2016
DOI: 10.1631/jzus.b1600266
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic acid sensitized colon cancer cells to chemotherapy under hypoxia by inhibiting MDR1 through HIF-1α

Abstract: Abstract:Objective: To explore the efficacy of ursolic acid in sensitizing colon cancer cells to chemotherapy under hypoxia and its underlying mechanisms. Methods: Three colon cancer cell lines (RKO, LoVo, and SW480) were used as in vitro models. 5-Fluorouracil (5-FU) and oxaliplatin were used as chemotherapeutic drugs. Cell viability and apoptosis were tested to evaluate the sensitivity of colon cancer cells to chemotherapy. The transcription and expression levels of hypoxia-inducible factor-1α (HIF-1α), mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 33 publications
3
9
0
Order By: Relevance
“…2D and G ). These findings are consistent with the observations of previous studies on HIF-1α, where HIF-1α downregulation was reported to inhibit the expression levels of VEGF and MDR1 in cancer cells ( 17 , 33 ). Notably, LV-H721 infection led to HIF-1 α knockout in the SMMC-7721 ×enograft tissues ( Fig.…”
Section: Discussionsupporting
confidence: 93%
“…2D and G ). These findings are consistent with the observations of previous studies on HIF-1α, where HIF-1α downregulation was reported to inhibit the expression levels of VEGF and MDR1 in cancer cells ( 17 , 33 ). Notably, LV-H721 infection led to HIF-1 α knockout in the SMMC-7721 ×enograft tissues ( Fig.…”
Section: Discussionsupporting
confidence: 93%
“…The angiogenic factor VEGFA is produced by active synovial fibroblasts and has been implicated in the pathogenesis of RA, being one of its most important biomarkers ( Taylor, 2002 ). Studies have revealed the chemosensitizing effects of ursolic acid in colon cancer ( Shan et al, 2016 ) and the protective effects of paeoniflorin against oxidative injury ( Song et al, 2017 ), both via suppression of VEGF signaling. Taken together, our results are in agreement with previous research showing the compound-target relationship between ursolic acid/paeoniflorin and each of LGALS3, STAT3, and VEGFA.…”
Section: Discussionmentioning
confidence: 99%
“…Ursolic acid can inhibit the expression of newborn VEGF and inhibit the accumulation of HIF-1 α and the expression of the MDR1 gene and protein under hypoxia. It has a sensitizing effect on chemotherapy of colon cancer cells [ 15 ].…”
Section: Discussionmentioning
confidence: 99%